Efecto de la Educación sobre el Crecimiento Económico de Ecuador, periodo 1970-2010; mediante un Modelo Econométrico de Series de Tiempo - Romero Romero, Erika Vanessa (2020)
A determinant of economic growth, without a doubt, is human capital; and education creates human capital. In Ecuador, educational statistics are not very encouraging, as the average years of education has not grown significantly in recent years, from 7.3 years, 2000, to 7.6 years, 2010, an increase of almost zero. Therefore, the main objective of this research is to estimate and analyze the effect of education in the short and long term on the economic growth of Ecuador in the period 1970-2010, using an OLS model and time series cointegration techniques. For this, an annual time series was used, which was obtained from the World Bank database (2020) and the Penn World Table database (9.1). The human capital index was used as a proxy for the variable education and GDP to explain economic growth. According to the results obtained, education has a positive influence on economic growth; Furthermore, there is a short-term and long-term relationship between education and economic growth; on the other hand, unidirectional causality was found in the sense of Granger that goes from education to economic growth. Therefore, it is recommended to strengthen the educational system through educational reforms aimed at improving and strengthening primary and secondary education, since it is in this period where children and young people acquire the necessary skills for their future academic development; such as the constant training of teachers to acquire a pedagogy that allows them to develop and enhance the skills, knowledge, and capacities of children from the first year of school, as well as increasing and prioritizing investment in education. .